Creative occupations as knowledge practices: Innovation and precarity in the creative economy - Hearn Greg (Cultural Science)
The ARC Centre of Excellence in Creative Industries and Innovation (herewith CCI) was established with two simple policy objectives. One was to assess anecdotal and boosterish claims about the growth rates of the creative industries, and hence, to measure the size of the creative industries contribution to gross domestic product (GDP). The other was to ascertain the contribution of the creative industries to employment. Preliminary research detailed in Cunningham and Higgs (2009) showed that the existing industrial classifications did not incorporate the terminology of the creative industries, nor did they disaggregate new categories of digital work such as video games. However, we discovered that occupational codes provide a much more fine-grained account of work that would enable us to disaggregate and track economic activity that corresponded to creative industries terminology. Thus was born one major centrepiece of CCI research – the tracking of national occupational codes in pursuit of measuring creative industries policy outcomes. This paper commences with some description of empirical work that investigates creative occupations; however, the real point is to suggest that this type of detailed, occupation-based empirical work has important theoretical potential that has not yet been fully expended (though see Cunningham 2013; Hearn and Bridgstock 2014; Bakhshi, Freeman and Higgs 2013; Hartley and Potts 2014).